Contents in tumor-educated platelets as the novel biosource for cancer diagnostics - Zhang, Qianru; Song, Xianrang; Song, Xingguo (Frontiers in Oncology, 2023)
Liquid biopsy, as a powerful non-invasive test, has been widely used in the field of cancer diagnosis and treatment. Platelets, the second most abundant cells in peripheral blood, are becoming one of the richest liquid biopsy sources with the capacity to systematically and locally respond to the presence of cancer, uptake and store circulating proteins and different types of nucleic acids, thereby called “tumor-educated platelets (TEPs)”. The contents in TEPs are altered significantly and specifically, empowering them with the potential as cancer biomarkers. The current review focuses on the alternation of the contents in TEPs including the coding and non-coding RNA and proteins, and their role in cancer diagnostics.